2017
DOI: 10.1111/jace.14971
|View full text |Cite
|
Sign up to set email alerts
|

Stability of rare‐earth‐doped spherical yttria‐stabilized zirconia synthesized by ultrasonic spray pyrolysis

Abstract: Phase stability is one of the crucial requirements for any material that can be used at elevated temperature applications such as thermal barrier coating (TBC). The most traditional TBC material, partially stabilized zirconia, limits the operating temperature due to its phase transformation. Conversely, the low thermal conductivity of fully stabilized zirconia (YSZ) may enable effective reduction in the surface temperature on the coated component, while avoiding deleterious phase transitions, although still be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Figure 2 and Figure show the DSC signals obtained from sintering Al‐doped Y 2 O 3 up to 1250℃ used for the measurement of both surface and grain boundary energies. Similar to the data obtained for interfacial energy measurements of undoped Y 2 O 3 and various other nanoceramic systems, exothermic heat effects starting above the calcination temperatures were observed 26,27,31,32 1) showed no changes in the crystal structure during the DSC experiments.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Figure 2 and Figure show the DSC signals obtained from sintering Al‐doped Y 2 O 3 up to 1250℃ used for the measurement of both surface and grain boundary energies. Similar to the data obtained for interfacial energy measurements of undoped Y 2 O 3 and various other nanoceramic systems, exothermic heat effects starting above the calcination temperatures were observed 26,27,31,32 1) showed no changes in the crystal structure during the DSC experiments.…”
Section: Resultssupporting
confidence: 83%
“…No references were found on modeling of the PIP process for CMCs, though experimental studies on this manufacturing process have been reported. Studies on polycarbosilanederived SiC ceramic 25 and SiC/SiC composite 26,27 have shown that porosity decreases and mechanical properties improve with the increasing number of PIP cycles. Zhu et al 28 show that increasing pyrolysis temperature and the concentration of SiC fillers in polycarbosilane polymer result in improved mechanical properties in two-dimensional Carbon/ SiC (C/SiC) composites fabricated using the PIP process.…”
mentioning
confidence: 99%
“…58 This is especially evident for the DSC curves of the samples with the smallest starting grain sizes, contrasting with previous data from similar experiments in the literature which show single DSC peaks of sintering. 32,59 Author Manuscript…”
Section: Author Manuscriptmentioning
confidence: 99%
“…Moreover, Nafsin et al have studied the stability of Lanthanum-gadolinium-yttria stabilized zirconia (La-Gd-YSZ) complex coating [25]. They found further increases in thermal stability, with retaining the sphere shape and nanoscale crystallite size up to 1000 • C for at least 3 h, while at 1100 • C the spheres started necking but the spheres were still in shape [25].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Nafsin et al have studied the stability of Lanthanum-gadolinium-yttria stabilized zirconia (La-Gd-YSZ) complex coating [25]. They found further increases in thermal stability, with retaining the sphere shape and nanoscale crystallite size up to 1000 • C for at least 3 h, while at 1100 • C the spheres started necking but the spheres were still in shape [25]. In this work, we used higher temperatures of 1200 and 1300 • C for the isothermal oxidation test on La-Gd-YSZ (Y-5 wt.%, Zr-65 wt.% and a little amount of other rare earth elements; La-0.15 wt.% and Gd-0.1 wt.%) coating.…”
Section: Introductionmentioning
confidence: 99%